2015
DOI: 10.5380/cep.v33i2.47233
|View full text |Cite
|
Sign up to set email alerts
|

QUALIDADE SANITÁRIA DE SURURU (Mytella guyanensis) BENEFICIADO POR COMUNIDADE QUILOMBOLA

Abstract: O objetivo deste trabalho foi avaliar as condições higiênico-sanitárias do processamento de sururu, por meio da caracterização microbiológica, parasitológica e físico-química das etapas do benefi ciamento. A análise microbiológica de coliformes totais, Escherichia coli (E. coli) e Staphylococcus aureus (S. aureus), foi realizada por método rápido de contagem por placas Petrifi lm™ e por método cromogênico, e para avaliação parasitológica, foram utilizados o exame direto e o método de Faust. Para obtenção da qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
2
1
Order By: Relevance
“…The number of unacceptable samples increased, with 88.9% (8) in precooked (control) mussels and counts ranging from 5 x 10 2 CFU/g to 4.8 x 10 6 CFU/g. The levels of CFU/g obtained were higher than those described by Freitas et al (2015), who reported that 33.33% of Charru mussels precooked by shellfish collectors was contaminated with S. aureus at levels above those permitted by law, and that the tools were also contaminated by E. coli in 11.11% of the samples.…”
Section: Original Articlecontrasting
confidence: 67%
See 2 more Smart Citations
“…The number of unacceptable samples increased, with 88.9% (8) in precooked (control) mussels and counts ranging from 5 x 10 2 CFU/g to 4.8 x 10 6 CFU/g. The levels of CFU/g obtained were higher than those described by Freitas et al (2015), who reported that 33.33% of Charru mussels precooked by shellfish collectors was contaminated with S. aureus at levels above those permitted by law, and that the tools were also contaminated by E. coli in 11.11% of the samples.…”
Section: Original Articlecontrasting
confidence: 67%
“…According to Freitas et al (2015), the main cause of contamination of processed bivalves is the lack of proper handwashing by shellfish collectors and improper cleaning of tools, which can cause contamination especially by coliforms and S. aureus. This is consistent with the present study where greater contamination of mussels was detected after their processing by fishermen, indicating that their hands and/or the tools used by the workers can be sources of recontamination of the product.…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation